RECRUITMENT OF PEOPLE WITH DISABILITIES, BETWEEN FEARS AND BENEFITS - Victoria-Mihaela BRÎNZEA; Carmen-Gabriela SECARĂ (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2014)
People with disabilities are often not considered as potential labour members, and they face over time, barriers related to their access on the labour market. Despite the legal provisions forbidding discrimination at the employment of this category of people, prejudices, fear and myths keep limiting the understanding and acceptance of disability for jobs everywhere. Employers are reluctant when it comes to recruit people with disabilities, their main concerns being related to the fact that people with disabilities are unable to work and that the costs associated with such employees would exceed the benefits. However, studies prove that employees with disabilities do not need high costs to adjust to their workplace; they are hardworking and trustworthy. Our paper aims at presenting an image of the situation of people with disabilities on the labour market, identifying the difficulties faced by them as well as a number of good practices of some companies, which successfully prove that, with a little bit of adjustment, the community of people with disabilities can offer talented and motivated employees.